Using habitat selection index for reserve planning and management for snub-nosed golden monkeys at landscape scale. (October 2018) - Wang, Pengcheng; Teng, Mingjun; He, Wei; Tang, Cheng; Yang, Jingyuan; Yan, Zhaogui
Highlights: An index of habitat selection was developed for Rhinopithecus roxellana . Potential habitat for R. roxellana was predicted and mapped. Only 22% of predicted habitat were within the current activity area and utilized. Clear guidance on reserve selection and management was provided. Abstract: Many wildlife species are known to actively select their habitat. Understanding habitat selection and use is crucial for conservation and management of endangered wildlife species. In this study, an index that can be used for reserve selection and management for the snub-nosed golden monkeys ( Rhinopithecus roxellana ), was developed . Environmental attributes of habitat and non-habitat sites of the Shennongjia District were analyzed. The relationship between habitat selection and effective range of the major variables were quantified. The results showed that elevation, distance to road and water, and vegetation were the most important contributors to the habitat selection index . Potential habitat areas of R. roxellana were predicted and mapped based on the index. Total area suitable as habitat for R. roxellana was estimated at 33, 970 ha in Shennongjia District. Only 22% of the estimated habitat was within the current activity area of the animal and utilized . At the landscape scale, conservation of R. roxellana should therefore focus on expanding the current reserve to encompass areas with large patches of potential suitable habitat, planning road constructions away from habitat areas, and restricting road traffics on existing roads to improve connectivity between patches of potential habitat . The habitat selection index can be used for predicting potential habitat areas for endangered wildlife species such as R. roxellana, and thus is of immediate interest to practitioners and policy makers of wildlife conservation in their conservation planning and management decision-making.